RANCANGAN TEKNIS DAERAH TANGKAPAN HUJAN UNTUK MENGURANGI PENGIKISAN BIDANG LERENG DAN MENCEGAH AIR LIMPASAN DENGAN METODE CROSS FALL PADA TEMPAT PENYIMPANAN TANAH PUCUK - Reinaldy, Wilmar; Nugroho, Yusanto; Razie, Fakhrur; Arifin, Yulian Firmana (EnviroScienteae, 2024)
Mining activities often cause environmental damage, such as landslides, floods and ecosystem changes. These activities include land clearing, top soil stripping, overburden stripping, coal excavation, coal transport and processing. It is necessary to have an activity as an effort to rehabilitate so that there is no sustainable environmental damage. Therefore topsoil storage must be carried out in order to return the post-mining area to green again. The consideration of replanting ex-mining areas uses a comprehensive environmental management strategy, especially in terms of handling nutrient-rich topsoil. Topsoil is peeled to a thickness of 0.5 – 1 meter using an excavator. Then it is stacked and stockpiled in a place that is safe from mining activities so that later it can be reused in reclamation activities. The purpose of this research is to obtain a technical design on the corner of the storage area to reduce the eroding impact of rain runoff or other mining activities. Where the method used is to calculate the erosion that occurs on each slope where the test is carried out with 4 different slope angles such as 20⁰, 25⁰, 30⁰ and 35⁰. After obtaining the erosion data, the researchers created an ideal design to reduce the impact by considering the balance aspects of the slope and the material itself. Where the recommended angle data obtained to reduce the eroding impact is 25⁰.